Sulfone as traceless activating group: Divergent synthesis of α-fluoroamides with C–F quaternary stereocenters - Jieqing Wu; Liying Fu; Renyi Diao; Longjun Nie; Chi Zhang; Yufeng Li; Chao Feng (Green Synthesis and Catalysis)
A novel approach to α-fluoroamides bearing a C–F quaternary stereocenter is reported herein. With sulfone installed as the activating group, an alkyl group as well as a fluorine atom was introduced successively under mild conditions. Subsequently, heterolytic fission of the C–S bond occurred smoothly under photoredox conditions to afford a tertiary radical, which then engaged in varied intramolecular cyclizations depending on substrate structure and condition applied, rendering sulfone an overall traceless activating group.